Biomechanical Analysis of Mawashi-Geri Technique in Karate: Review Article - Hariri, Salar; Sadeghi, Heydar (International Journal of Sport Studies for Health, 2018)
Mawashi-Geri Jodan technique (circular kicking to the opponent’s head), is one of the most commonly used techniquesin the Karate, especially in the combat style. Although the speed of the implementation of the technique plays an important role in gaining points, there is no specific pattern for optimal performance of the technique. In this research, it was aimed at reviewing the results of the previous research that has been conducted on the effective issues relating to the success of this technique performance. The related articles were searched in ScienceDirect, PubMed, Google Scholar by considering the words like Karate, biomechanics, kinetic and kinetic analysis, EMG of Mawashi-Geri and EMG of kick. In the years ranging from 2000 to 2018, the findings of the research showed that the quadriceps muscles, especially rectus femoris muscle, played a major role in the efficacy of technique performance. Keeping the knee upward while rotating the body, the technique will be performed faster due to closer distance toward the opponent. Therefore, Karate player can obtain the required score more easily and quickly. It seems that the use of this pattern will be effective in performing the technique of Mawashi-Geri in Karate.